2017
DOI: 10.1002/sd.1701
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Waste Generation Efficiency in EU Regions towards Sustainable Environmental Policies

Abstract: This paper employs data envelopment analysis (DEA) to consider waste generation at a regional level in the European Union (EU). By doing so both good and bad outputs are taken into account and different frameworks are designed. Five parameters (waste generation, employment rate, capital formation, GDP and population density) are used for 172 EU regions and for the years 2009, 2011 and 2013. In this way four frameworks have been designed, each with different inputs and outputs. The results show the most efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Governmental policies can guide producers' waste management behavior (Bao, Lu, Chi, Yuan, & Hao, 2019; Halkos & Petrou, 2018; Liu, Gong, Wang, Lai, & Zhu, 2019; McCauley, 2015; Wei, Li, Liu, & Wu, 2019; Yuan & Yang, 2020; Zhang et al, 2019). To promote C&D waste management, relevant policies have been implemented in many countries (Ajayi & Oyedele, 2018; Bao & Lu, 2020; Chen & Lu, 2017; Di Maria, Eyckmans, & Van Acker, 2018; Tam & Lu, 2016; Wang, Wu, Tam, & Zuo, 2019; Wu et al, 2020; Wu, Zuo, Yuan, Zillante, & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Governmental policies can guide producers' waste management behavior (Bao, Lu, Chi, Yuan, & Hao, 2019; Halkos & Petrou, 2018; Liu, Gong, Wang, Lai, & Zhu, 2019; McCauley, 2015; Wei, Li, Liu, & Wu, 2019; Yuan & Yang, 2020; Zhang et al, 2019). To promote C&D waste management, relevant policies have been implemented in many countries (Ajayi & Oyedele, 2018; Bao & Lu, 2020; Chen & Lu, 2017; Di Maria, Eyckmans, & Van Acker, 2018; Tam & Lu, 2016; Wang, Wu, Tam, & Zuo, 2019; Wu et al, 2020; Wu, Zuo, Yuan, Zillante, & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The works of various authors are devoted to the issues of sustainable development of regions and waste management. Studies are being carried out related to the formation of a sustainable environmental policy and the development of a methodology for assessing the efficiency of waste generation in EU regions (Halkos & Petrou, 2018). Developing countries are also the focus of research on sustainable waste management (Waqas, 2019).…”
Section: Recycling As a Component Of Sustainable Development Of Regional Systemsmentioning
confidence: 99%
“…Previous studies have shown that the performance of enterprises in terms of environmental protection has an impact on the competitiveness of the semiconductor industry [37]. Halkos and Petrou [49] studied EU waste emissions from the perspective of regional development. ey found that energy use, CO 2 emissions, solid waste generation, wastewater discharge, and exhaust gas emissions were common sources of environmental pollution [50].…”
Section: Data Collectionmentioning
confidence: 99%